Simple and efficient thermal calibration for MEMS gyroscopes. (May 2018) - Nez, Alexis; Fradet, Laetitia; Laguillaumie, Pierre; Monnet, Tony; Lacouture, Patrick
Highlights: An easy protocol to perform a thermal gyroscope calibration is proposed. This calibration procedure is performed without any need for temperature control. The proposed simple calibration method leads to a similar accuracy than those obtained from the manufacturer, known to be performed by controlled rotation on a thermal chamber. An analysis of uncertainty propagation highlights that offsets variability is the major source of error over the computed rate of rotation from the tested sensors. This result leads to a simplified calibration method. Abstract: Gyroscopes are now becoming one of the most sold MEMS sensors, given that the many applications that require their use are booming. In the medical field, gyroscopes can be found in Inertial Measurement Units used for the development of clinical tools that are dedicated to human-movement monitoring. However, MEMS gyroscopes are known to suffer from a drift phenomenon, which is mainly due to temperature variations. This drift dramatically affects measurement capability, especially that of cheap MEMs gyroscopes. Calibration is therefore a key factor in achieving accurate measurements. However, traditional calibration procedures are often complex and require costly equipment. This paper therefore proposes an easy protocol for performing a thermal gyroscope calibration. In this protocol, accuracy over the angular velocity is evaluated by referring to an optoelectronic measurement, and is compared with the traditional calibration performed by the manufacturer. The RMSE between the reference angular velocity and that obtained with the proposed calibration was of 0.7°/s, which was slightly smaller than the RMSE of 1.1°/s achieved by the manufacturer's calibration. An analysis of uncertainty propagation shows that offset variability is the major source of error over the computed rate of rotation from the tested sensors, since it accounts for 97% of the error. It can be concluded that the proposed simple calibration method leads to a similar degree of accuracy as that achieved by the manufacturer's procedure.